TRANSFORMASI TRANSPORTASI: DAMPAK LAYANAN ONLINE TERHADAP PENGEMUDI KONVENSIONAL DI KOTA PEMATANGSIANTAR - Fikri Ari Al-Fattah; Hana Tori Zahira; Lila Pelita Hati; Lestari Dara Cinta Utami Ginting (JISOS: JURNAL ILMU SOSIAL, 2024)
This study aims to investigate the perceptions of people in Pematangsiantar City towards changes in transportation choices, particularly between conventional and online transportation. A qualitative approach was used in data collection, through direct interviews and observational surveys in Pematangsiantar City. The data collected was then analyzed to identify the factors influencing these changes and their impact on daily life. The results showed a significant shift in people's preference towards online transportation, influenced by considerations of time efficiency and convenience. In addition, the research identifies the challenges and opportunities that come with this change, providing an in-depth look at the dynamics of transportation transformation in Pematangsiantar City. The impact of these changes is also seen in the decline in the income of conventional transportation drivers such as Angkot and Becak. The implications of these findings can be used by the government and transportation service providers to design more adaptive policies and improve service quality to optimally meet community needs